Using real time process measurements to reduce catheter related bloodstream infections in the intensive care unit. Issue 4 (1st August 2005) - Wall, R J; Ely, E W; Elasy, T A; Dittus, R S; Foss, J; Wilkerson, K S; Speroff, T
Abstract : Problem: Measuring a process of care in real time is essential for continuous quality improvement (CQI). Our inability to measure the process of central venous catheter (CVC) care in real time prevented CQI efforts aimed at reducing catheter related bloodstream infections (CR-BSIs) from these devices. Design: A system was developed for measuring the process of CVC care in real time. We used these new process measurements to continuously monitor the system, guide CQI activities, and deliver performance feedback to providers. Setting: Adult medical intensive care unit (MICU). Key measures for improvement: Measured process of CVC care in real time; CR-BSI rate and time between CR-BSI events; and performance feedback to staff. Strategies for change: An interdisciplinary team developed a standardized, user friendly nursing checklist for CVC insertion. Infection control practitioners scanned the completed checklists into a computerized database, thereby generating real time measurements for the process of CVC insertion. Armed with these new process measurements, the team optimized the impact of a multifaceted intervention aimed at reducing CR-BSIs. Effects of change: The new checklist immediately provided real time measurements for the process of CVC insertion. These process measures allowed the team to directly monitor adherence to evidence-based guidelines. Through continuous process measurement, the team successfully overcame barriers to change, reduced the CR-BSI rate, and improved patient safety. Two years after the introduction of the checklist the CR-BSI rate remained at a historic low. Lessons learnt: Measuring the process of CVC care in real time is feasible in the ICU. When trying to improve care, real time process measurements are an excellent tool for overcoming barriers to change and enhancing the sustainability of efforts. To continually improve patient safety, healthcare organizations should continually measure their key clinical processes in real time.